The Improvement Of Electrical Power Generated By Pump As Turbine Using Guide Vane - Dede Lia Zariatin; Taruna Taruna; Danies Seda; Agri Suwandi; Ismail Ismail (Journal of Applied Sciences and Advanced Technology, 2020)
One of the problems faced by micro hydropower plant, including Pump as Turbine is low efficiency. Pump as Turbine (PAT) is one of micro-hydro power plant that uses a centrifugal pump as the turbine and modifies the pump motor to become a generator. Researches tried to improve the PAT efficiency by modifying the impeller and pump housing in order to optimize the flow that rotates the generator shaft. However, there is still another possibility of modifying and improving the water flow by using a regulating or guide vane. This research aims to improve PAT efficiency by conditioning the water inlet using a guide vane in a vertical direction. The regulating vane with a diameter of 56 mm has four vanes made of stainless steel. The vane is adjustable so that the vane opening can be regulated. In this research, the vane opening was setting at 0°, 30°, 45°, and 65°. The experimental test was performed at a PAT power plant's laboratory scale with a head of 3.7 m above the ground. The regulating vane was placed on 260 and 400 mm above the PAT. It showed that the power increased 7% when the guide vane placed 400 mm above the pump shaft with a 45° of vane opening.